Repurposing FDA-approved disulfiram for targeted inhibition of diphtheria toxin and the binary protein toxins of Clostridium botulinum and Bacillus anthracis - Borho, Joscha; Kögel, Merle; Eckert, Amelie; Barth, Holger (Frontiers in Pharmacology, 2024)
Many bacteria act pathogenic by the release of AB-type protein toxins that efficiently enter human or animal cells and act as enzymes in their cytosol. This leads to disturbed cell functions and the clinical symptoms characteristic for the individual toxin. Therefore, molecules that directly target and neutralize these toxins provide promising novel therapeutic options. Here, we found that the FDAapproved drug disulfiram (DSF), used for decades to treat alcohol abuse, protects cells from intoxication with diphtheria toxin (DT) from Corynebacterium diphtheria, the causative agent of diphtheria, lethal toxin (LT) from Bacillus anthracis, which contributes to anthrax, and C2 enterotoxin from Clostridium botulinum when applied in concentrations lower than those found in plasma of patients receiving standard DSF treatment for alcoholism (up to 20 µM). Moreover, this inhibitory effect is increased by copper, a known enhancer of DSF activity.LT and C2 are binary toxins, consisting of two non-linked proteins, an enzyme (A) and a separate binding/transport (B) subunit. To act cytotoxic, their proteolytically activated B subunits PA63 and C2IIa, respectively, form barrel-shaped heptamers that bind to their cellular receptors and form complexes with their respective A subunits LF and C2I. The toxin complexes are internalized via receptor-mediated endocytosis and in acidified endosomes, PA63 and C2IIa form pores in endosomal membranes, which facilitate translocation of LF and C2I into the cytosol, where they act cytotoxic. In DT, A and B subunits are located within one protein, but DT also forms pores in endosomes that facilitate translocation of the A subunit.If cell binding, membrane translocation, or substrate modification is inhibited, cells are protected from intoxication. Our results implicate that DSF neither affects cellular binding nor the catalytic activity of the investigated toxins to a relevant extend, but interferes with the toxin pore-mediated translocation of the A subunits of DT, LT and C2 toxin, as demonstrated by membrane-translocation assays and toxin pore conductivity experiments in the presence or absence of DSF. Since toxin translocation across intracellular membranes represents a central step during cellular uptake of many bacterial toxins, DSF might neutralize a broad spectrum of medically relevant toxins.